INCREASING ADOLESCENT KNOWLEDGE ABOUT RATIONAL COMMON COLD SELF-MEDICATION: PENINGKATAN PENGETAHUAN REMAJA TENTANG SWAMEDIKASI COMMON COLD YANG RASIONAL - Ristian Octavia, Devi; Arviana Ekawati, Dea; Puspita Lestari, Trijati; Majid, Abdul (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Knowledge of self-medication is associated with engaging in self-medication. Choosing the wrong common cold medication not only fails to deliver the best results but also leads to higher treatment expenses. Based on previous research in 2023, it was reported that 19.88% student in Yogyakarta had low knowledge about common cold self-medication. Objective: This service activity aims to increase teenagers' knowledge about rational self-medication for common cold. Method: The activity involved directly educating partners about rational self-medication for the common cold through the use of posters and leaflets, followed by their understanding with pre-tests and post-tests. Results: Following schooling, partners' knowledge increased. Conclusion: Education can raise public awareness of rational self-medication for the common cold, allowing people to make more informed decision when taking medications in their regular self-medication practices.